Visible Light Spectroscopy of W14+ Ions in an Electron Beam Ion Trap - Ben Niu; Zhaoying Chen; Jihui Chen; Yanting Li; Fangshi Jia; Bingli Li; Zhencen He; Jun Xiao; Yaming Zou; Ke Yao (Atoms)
In this work, the visible lines of <semantics>W14+</semantics> ions in the wavelength range of 400–650 nm are investigated experimentally and theoretically. The experiments were performed in a low-energy electron beam ion trap. The simulated spectra of <semantics>W14+</semantics> ions (Nd-like) were obtained from atomic structure computations in combination with a collisional–radiative model. Overall, there is a reasonable similarity between the measurements and the results of the simulations, and most of the twelve observed spectral lines associated with <semantics>W14+</semantics> were tentatively identified.